Effect of Sterility Values and Retort Temperatures on the Antioxidant Activities, Soluble Protein, and PH of Canned Mushroom. - PURSITO, DIDIK JOKO; PURNOMO, EKO HARI; FARDIAZ, DEDI; HARIYADI, PURWIYATNO (Current Research in Nutrition & Food Science, 2022)
This research aimed to study the effect of sterility values on antioxidant activity, soluble protein, and pH of canned Agaricus bisporus mushrooms processed at various retort temperatures (115, 121, and 130 °C) and processing times (2-97 minutes). The canning process was carried out by following commercial production procedures in one of the mushroom canning industries. Measurement of heat penetration into the product was carried out using a standard protocol. The sterility values (F0-value) were calculated using the General Method. Our results indicate that antioxidant activity, soluble protein contents, and pH of canned mushrooms are not only affected by sterility value but also by the combination of temperature and time used to process the product. At the same F0-value of 10 minutes, retorting of A. bisporus mushroom at a higher retort temperature (130 °C) resulted in higher antioxidant activity (RSA 73.73%) and soluble protein contents (24.1 mg/g), but resulted in lower pH-value as of (5.5±0.04 in drained liquid and 6.52±0.21 in drained solid) than other retort temperature of 115 and 121 °C.Since retort temperature is crucial parameters of chemical quality of product attributes in the canning industry, the selection of higher temperatures and shorter time of retorting will have a positive impact on quality parameter such as antioxidant activity and total soluble protein.